Amy, Susie, Tessie - Cayado, Tony (Sampaguita Pictures, 2005)
Three sisters, Amy, Susie, and Tessie, go through the trials and triumphs of teenage life together. Having lost their mother, the three take on loving role as the women in their father's life and date on him all time. At the same time, the three discover for themselves the sweeter side of growing up; having suitors and falling in love. Everything seems fine with their father decides to pursue a relationship with another woman, and hides it from them.